Les villae gallo-romaines dans le territoire proche d’Augustonemetum – Clermont-Ferrand - Bertrand Dousteyssier; Maxence Segard; Frédéric Trément (Revue Archéologique du Centre de la France)
This article aims to provide a survey of the research that has been conducted, up until now, on the gallo-roman villae located in the Augustonemetum area. The multiple research tools and methods (bibliography, data gathered through excavating, systematic field walking and aerial surveys) allow us to present, for the very first time, a thorough table of population density in the Limagne plain during the Roman period. The villae were very numerous and had a deep and durable impact on their surroundings. They are studied from dynamic and topological points of view. The results of the first analyses performed on the marble found in these villae show how important this material was; the results also pinpoint various strategies as far as supply was concerned..